2010
DOI: 10.1007/s00442-010-1830-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant defences and the role of epibiosis in mediating within-plant feeding choices of seagrass consumers

Abstract: Within-plant variation in susceptibility to herbivory can significantly influence the ecological and evolutionary consequences of plant-herbivore interactions. Seagrasses are marine angiosperms characterised by substantial intra-individual differences in multiple traits, such as nutrients, chemical and structural defences and epibiotic load, all of which can strongly influence herbivore preferences. We quantified the within-plant feeding choices of the two main consumers of the temperate seagrass Posidonia oce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 83 publications
2
30
0
Order By: Relevance
“…Montague et al 1991, Greenway 1995Alcoverro et al 1997, Vergés et al 2011. Detrital leaves had approximately half the nitrogen content of green leaves alone and a nearly 2-fold higher C:N ratio, but consumption rates of both types of leaves without the epiphytes were not significantly different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Montague et al 1991, Greenway 1995Alcoverro et al 1997, Vergés et al 2011. Detrital leaves had approximately half the nitrogen content of green leaves alone and a nearly 2-fold higher C:N ratio, but consumption rates of both types of leaves without the epiphytes were not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…This issue has been inadequately investigated, although it can have important consequences for the functioning of ecosystems, depending on the dif ferent interactions between grazers and seasonal changes in the standing plant biomass, production (Duarte 1989, Kaldy & Dunton 2000, and leaf loss dynamics (Francour 1990, Romero et al 1992. Previous studies have suggested that sea urchins preferentially feed on epiphytes (Verlaque & Nédelec 1983, Shepherd 1987, Tomas et al 2005a, Vergés et al 2011, possibly due to their C:N ratios and the absence of refractory plant material. Also, the composition of the epiphyte assemblage may influence consumption through changes in the abundance of certain species or morphological groups (Gacia et al 1999, Thacker et al 2001, Prado et al 2007b, 2008b.…”
Section: Introductionmentioning
confidence: 99%
“…Preferences of seagrass consumers may thus be influenced by factors other than N, such as fibre content or leaf-fracture properties, which may be more relevant. Vergés et al (2007aVergés et al ( , 2011 found that sea urchins preferentially consumed the most nutritious but less chemically defended leaf tissues only when structural defences were removed in artificial diet experiments. Along the same lines, Prado & Heck (2011) suggested that structural plant features are the most important factors driving discrimination between seagrass species by omnivorous fish, whereas strict herbivores make feeding decisions influenced by nutritional characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mechanical resistance by leaf toughening have been commonly reported as an effective anti-herbivore defence in terrestrial ecology because it limits the ability of the herbivores to shear or tear the leaves for their intake (Grime et al 1996, Wright & Vincent 1996, Pennings et al 1998, Lucas et al 2000, Díaz et al 2001, Sanson et al 2001, Siska et al 2002, Cingolani et al 2005, Sanson 2006. Recent publications on traits mediating feeding choices of seagrass consumers suggest that structural traits of seagrass leaves (related to leaf mechanical resistance) may play an important role in regulating the plant−herbivore interactions in seagrass ecosystems (Prado & Heck 2011, Vergés et al 2011. Other leaf traits, such as the synthesis of chemical feeding deterrents (Zapata & McMillan 1979, McMillan et al 1980, Vergés et al 2007a or nitrogen content (Ver gés et al 2007b, Prado et al 2010, Prado & Heck 2011, have also been reported to influence food selection by seagrass consumers, since their variation may reduce plant quality as food, making leaves less palatable by conferring low attractiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as plant availability and accessibility, plant nutritional quality, human pressure on herbivore populations, and herbivore recruitment and predation risk have all been shown to influence the intensity of herbivory on seagrasses meadows (Prado et al, 2008a(Prado et al, , 2009(Prado et al, , 2010. In addition, it has been shown that as many terrestrial plants and marine algae, seagrasses chemically deter herbivores using secondary metabolites, although inhibition varies among consumers (Verg es et al, 2007(Verg es et al, , 2011. Therefore seagrasseherbivore interactions are further complicated and studies are needed to improve our knowledge of the mechanisms controlling feeding decisions and consumption rates of major herbivores in seagrass ecosystems .…”
Section: Introductionmentioning
confidence: 98%